Soft probes of p+Pb and Pb+Pb collisions in the ATLAS experiment at the LHC. (April 2015) - Radhakrishnan, S
Abstract: Collective flow and azimuthal correlation measurements of particles in the p T region ≲ 10 GeV provide valuable information in constraining the initial conditions and expansion dynamics of the system produced in heavy-ion collisions. ATLAS collaboration has recently measured correlations between flow harmonics in Pb+Pb collisions at = 2.76 TeV, using an event-shape selection procedure, and has separated the components arising from linear and non-linear hydrodynamic evolution in higher order harmonics ( v 4 and v 5 ). A brief overview of these results are presented in these proceedings. Recently, azimuthal correlations extending to large pseudorapidity differences ("ridge"), similar to that seen in heavy-ion collisions, was observed in p +Pb collisions at LHC. These proceedings also present a measurement of the Fourier harmonics associated with the ridge correlations ( v 1 to v 5 ) in p +Pb collisions at = 5.02 TeV by ATLAS collaboration. The results are compared with v n in Pb+Pb collisions at = 2.76 TeV with similar event multiplicities. Reasonable agreement is observed after accounting for the difference in the average p T of particles produced in the two collision systems, consistent with a recent hydrodynamic calculation.